Hubungan Pengetahuan dan Sikap Kerja Dengan Tindakan Pencegahan K3 di Laboraturium Tata Boga SMK Negeri 8 Surabaya: Hubungan Pengetahuan dan Sikap Kerja Dengan Tindakan Pencegahan K3 - Afrinda Sundari; Diana Evawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This title was chosen because Occupational Safety and Health (OSH) is a fundamental aspect of the modern workplace, both in terms of employee protection and the sustainability of company operations. Therefore, a discussion of OSH is highly relevant to support efforts to create a safe, healthy, and sustainable work environment. This research used a quantitative approach. The population was students of SMK Negeri 8 Surabaya, and questionnaires were distributed to over 99 respondents. Data analysis techniques used included validity testing, reliability testing, T-tests, and correlation analysis using SPSS version 22. The results showed that the majority of respondents had good knowledge of Occupational Safety and Health (OSH) and consistently demonstrated good preventive measures in laboratory practice. Of the total of over 99 respondents, 97 respondents (97.98%) had good knowledge and also implemented OSH preventive measures effectively. Meanwhile, only 2 respondents (2.02%) had poor knowledge, and of these, each was divided between those who performed well and those who did not.